Early Christian encounters with town and countryside: essays on the urban and rural worlds of early Christianity - Tiwald, Markus; Zangenberg, Jürgen (Novum testamentum et orbis antiquus, 2021)
Ever since Jesus walked the hills of Galilee and Paul travelled the roads of Asia Minor and Greece, Christianityhas shown a remarkable ability to adapt itself to various social and cultural environments. Recent research hasdemonstrated that these environments can only be very insufficiently termed as "rural" or "urban". Neither wasJesus' Galilee only rural, nor Paul's Asia only "urban".On the background of ongoing research on the diversity of social environments in the Early Empire, this volumewill focus on various early Christian "worlds" as witnessed in canonical and non-canonical texts. How did EarlyChristians experience and react to "rural" and "urban" life? What were the mechanisms behind thisadaptability?Papers will analyze the relation between urban Christian beginnings and the role of the rural Jesus-tradition. Inwhat sense did the image of Jesus, the "Galilean village Jew", change when his message was carried into thecities of the Mediterranean world from Jerusalem to Athens or Rome? Papers will not only deal with variouspersonalities or literary works whose various attitudes towards urban life became formative for futureChristianity. They will also explore the different local milieus that demonstrate the wide range of Christiancultural perspectives.